Build a Better Personal Abilities for a Sustainable Motivation: a Community Services in Penang, Malaysia: - Arijanto, Agus; Soelton, Mochamad; Bagaskara, Muhammad Adrian; Karyatun, Subur; Supryadi, Didy Ika; Arief, Harefan; Rahmad, Khozaeni Bin (Indonesian Journal of Society Development, 2024)
The aim of this community service is to empower informal workers and learning sector facilitators by strengthening the individual potential of the Indonesian Community Association (PERMAI) Pulau Pinang with a differentiated learning approach that favors the informal sector workers themselves, as well as an effort to adapt the adjustment process to the work community which exists. With minimal levels of education and skills, these job seekers have to compete with each other. To alleviate poverty, the government implemented a program to place Indonesian Migrant Workers (TKI) abroad. The government's role in this program is focused on aspects of training, protection and providing various conveniences to related parties, especially TKI and Indonesian Migrant Worker Placement Services Companies (PJTKI). Stage 1: Map and collect data on initial partner conditions; Stage 2, Socialization through discussions with partners regarding implementation preparations, implementation time, members involved and service topics at Partners; Stage 3: Training and empowerment of differentiated learning and learning pattern approaches that focus on increasing productivity levels; Stage 4: Assistance in implementing learning approaches to learning patterns that favor increasing productivity levels; Stage 5: monitor and evaluate all partner activities; Stage 6: Follow-up on program implementation